2014
DOI: 10.1155/2014/835485
|View full text |Cite
|
Sign up to set email alerts
|

Nitro Derivatives of Naturally Occurring β-Asarone and Their Anticancer Activity

Abstract: β-Asarone (2, 4, 5-trimethoxy-(Z)-1-propenylbenzene) was obtained from Acorus calamus. Nitration of β-asarone with AgNO2/I2 in ether yielded 1-(2, 4, 5-trimethoxy phenyl)-2-nitropropene (1) but with NaNO2/I2 in ethylene glycol obtained 1-(2, 4, 5-trimethoxy phenyl)-1-nitropropene (2). Compound 2 was prepared for the first time and characterized using IR, 1H-NMR, 13C-NMR, and GC-MS spectra and it was converted into 1-(2, 4, 5-trimethoxy) phenyl-1-propanone (3) using modified Nef reaction. Based on 1D NOESY expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…reported the anti-cancer assay of nitro derivatives of (β)-asarone using PC-3 (prostate cancer) cell line along with four other different types of human cancer cell lines by using MTT assay. The nitration derivative compounds of (β)-asarone exhibited an increase in activity compared to (β)-asarone confirming its cytotoxic activity in all the cell lines [34] ( Table 1 ; Figs. 4 and 5 ).…”
Section: Main Textmentioning
confidence: 63%
See 1 more Smart Citation
“…reported the anti-cancer assay of nitro derivatives of (β)-asarone using PC-3 (prostate cancer) cell line along with four other different types of human cancer cell lines by using MTT assay. The nitration derivative compounds of (β)-asarone exhibited an increase in activity compared to (β)-asarone confirming its cytotoxic activity in all the cell lines [34] ( Table 1 ; Figs. 4 and 5 ).…”
Section: Main Textmentioning
confidence: 63%
“… [33] Prostate cancer (PC-3 cells) Nitro derivatives of (β)-asarone (1.56–200) μM ↓ in the cell viability (MTT assay). [34] Neuroblastoma (IMR-32 cells) Cervical cancer (HeLa cells) Synovial cancer (SW982 cells) Breast cancer (MCF-7 cells) Macrophage cancer (P338D1 and J774 cells) Novel lectins from Acorus species (1.0–10) μg/ml ↓ in the cell viability ( 3 H-thymidine incorporation). [35] T cell lymphoma (A20 cells) B cell lymphoma (WEHI-279 cells) Cervical cancer (HeLa cells) Green silver nanoparticles synthesized from A. calamus (25, 50, 75, 100, 125, 150, 175 and 200 μg/ml) Anti-proliferative effect (% inhibition of cell proliferation through MTT assay).…”
Section: Main Textmentioning
confidence: 99%
“…10-Octadecenoic acid methyl ester decrease blood cholesterol and has antioxidant, antibacterial, and antifungal activities (Asghar & Choudahry, 2011). Asarone possess antioxidant activity (Cho, Kim, Kong, Yang, & Park, 2002;Devi, Mali, Rahee, & Belinda, 2014), adipogenesis inhibitory effect (Lee et al, 2011), antimicrobial (Devi & Ganjewala, 2009), stress reduction (Manikandan & Devi, 2005), and anticancer activities (Shenvi, Diwakar, & Reddy, 2014;Wang, Ouyang, & Lin, 2018). 9-Octadecynoic acid possess anti-inflammatory, cardiotonic, antibacterial, and analgesic activities (Kokila, Elavarasan, & Sujatha, 2016).…”
Section: Preparation Of Ligand and Oncoprotein Structurementioning
confidence: 99%
“…Studies have shown that βasarone has anti-cancer functions in colorectal cancer (Liu Wang et al, 2013;Zou et al, 2012), gastric cancer (Wu et al, 2015), lung cancer (Wang Ouyang et al, 2018), lymphoma (Lv et al, 2019) hepatocellular arcinoma (Stegmuller et al, 2018) and glioblastomas (Li L et al, 2018;Qi et al, 2015;Wang et al, 2017). It has been reported that nitro derivatives of β-asarone exert also anti-proliferative effects in prostate cancer cells (PC-3), neuroblastoma (IMR-32) cells, cervical cancer (HeLa) cells, synovial cancer (SW982) cells and breast cancer (MCF-7) cells (Shenvi et al, 2014). Aqueous and ethanolic extracts of A. calamus has been also reported to reduce the cell viability in breast cancer MDA-MB-435S cells and liver carcinoma Hep3B cells (Venkatadri, Guha, Kumar, & Lazar, 2009).…”
Section: Introductionmentioning
confidence: 99%